Re-imagining higher education leadership – in conversation with South African female deputy vice-chancellors - Moodly, Adele L.; Toni, Noluthando M. (Faculty of Education, University of the Free State, 2017)
Part of the decolonisation and transformation of higher education institutions is the re-construction of its leadership. This requires not only a review but also a dissolution of traditions, conventions and organisational forms that universities have inherited, including a re-imagining of leadership in higher education. Equity in representation of women in leadership has been acknowledged locally and internationally as part of the transformation agenda towards sustainable leadership. The authors argue that decolonisation and transformation are not mutually exclusive processes in the South African context, but that transformational leadership is part of the decolonisation process. This should embrace women’s ways of leadership in reconstructing leadership. The paper reflects on empirical data from personal interviews with three deputy-vice-chancellors on their journeys to leadership, with a focus on psychological and cultural factors (at the micro and meso levels), their career-pathing, personal characteristics and their experiences. These experiences are considered in the context of literature on women and leadership, using critical discourse analysis. It gives insight into the pathways that women often follow and provokes us to re-imagine the construct of “leadership”. The paper concludes with recommendations on the impact of psychological and cultural factors and the importance of the implementation of transformative policies, affirming male and female role models, institutional support structures and career planning which should form part of the decolonisation and transformation of conventions in capacity-building towards equity and sustainable leadership.
Keywords: Transformational leadership; Decolonisation; Personal life experiencies; Women's journeys